Fiscal Sustainability : A 21st Century Guide for the Perplexed - Tanner, Evan. (Washington, D.C. : International Monetary Fund, 2013)
This paper critically reviews recent work regarding the sustainability of public debt. It argues that Debt Sustainability Analyses (DSAs) should be more than mere mechanical simulation exercises. Instead, a DSA should be linked to some objective regarding the distribution of fiscal burdens and distortions over time (in the tradition of Barro's 1979 tax smoothing objective). The paper discusses objective functions that yield simple and transparent fiscal policy rules.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet